2018
DOI: 10.1111/bju.14553
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nonbacterial prostate inflammation in a rat model is associated with changes of gut microbiota that can be modified with a galactoglucomannan‐rich hemicellulose extract in the diet

Abstract: ObjectivesTo investigate dietary effects on the gut microbiota composition in a rat model of nonbacterial chronic prostate inflammation (CPI). Materials and methodsNonbacterial CPI was induced in the Wistar rat strain with subcutaneous testosterone and 17b-oestradiol (E 2 ) hormone pellets for 18 weeks. Rats with placebo pellets served as healthy controls. Rats with CPI were stratified into two groups, which drank either plain tap water (control group) or tap water supplemented with 2% galactoglucomannan-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 67 publications
3
34
0
Order By: Relevance
“… Shoskes et al (2016) reported that the gut microbiota of CNP patients showed lower alpha diversity and higher counts of Varibaculum . Konkol et al (2019) found increase of Rikenellaceae , Odoribacter , and Clostridiaceae , as well as decrease of Bacteroides uniformis , Lactobacillus , and Lachnospiraceae , in the gut microbiota of CNP rats. In this study, 16S rDNA sequencing was performed to reveal the structural changes of the gut microbiota in CNP rats.…”
Section: Introductionmentioning
confidence: 78%
“… Shoskes et al (2016) reported that the gut microbiota of CNP patients showed lower alpha diversity and higher counts of Varibaculum . Konkol et al (2019) found increase of Rikenellaceae , Odoribacter , and Clostridiaceae , as well as decrease of Bacteroides uniformis , Lactobacillus , and Lachnospiraceae , in the gut microbiota of CNP rats. In this study, 16S rDNA sequencing was performed to reveal the structural changes of the gut microbiota in CNP rats.…”
Section: Introductionmentioning
confidence: 78%
“…This study also indicates that prostate inflammation is associated with specific changes in the gut microflora, and hence with changes in SCFA levels. [ 61 ]. Additionally, it can be mentioned that caproic acid is one of the compounds found in saw palmetto, which is used in natural BPH therapy [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF signaling pathway plays an important role in psoriasis, and modified hemicellulose suppresses VEGF-induced angiogenesis (Malecic and Young, 2016;Zhu et al, 2017). Chronic inflammation is relevant to alterations of the intestinal microbiota that can be modified with hemicellulose (Konkol et al, 2019).…”
Section: Discussionmentioning
confidence: 99%